Morphology and Anatomy Histology of Brittle Star (Ophiocoma dentata) - Muyassaroh; Sulistiyawati; Luthfi, Muhammad Ja’far (Proceeding International Conference on Science and Engineering, 2021)
Abstract. This study aims to know the anatomy structure of the Morphology down to the and Histology of the Brittle star (Ophiocoma dentata). Brittle star is one of the Echinodermata phylum whose ecosystem is on a coral reefs, coral floors and hiding behind corals. Animal removal was made by observation of Nguyahan beach’s coral floor, at the same time as the site of morphology, followed by morphological and anatomic observations using stereo microscopes at the Zoology Lab of UIN Sunan Kalijaga, histological research using the eosin-hematoxylin method was also carried out in the same place. The results of the morphological observations of the star were obtained data on habitat, distribution,reproduction, a type of food, adaptation, movement and structure in the dorsal and ventral areas. While observation of the anatomy of the Brittle star (Ophiocoma dentata), data was obtained data on both horizontal and vertical disks, and leg structures by surgery. And the anatomical data of histology with eosin-hematoxylin got results on the disk, arms and spikes.